NASIONALISME SISWA KRISTEN DI KAWASAN TIMUR INDONESIA (STUDI TERHADAP WAWASAN KEBANGSAAN SISWA SMA DI POSO SULAWESI TENGAH) - muhammad dachlan; moh dulkiah; mustolehudin mustolehudin (Harmoni, 2020)
The cultivation of nationalism is very important for the younger generation, including students throughout the archipelago. National pride is the basic capital to build a nation state regardless of ethnicity, language, and religion followed by high school students. This article aims to determine 1) the national perception of Christian students in Central Sulawesi, Kab. Poso; 2) and explore what factors shape the national perceptions of Christian students in the region. By using the quantitative description method, in this study the following findings were obtained: The sense of state defense from the research sample is known to be 91%, maintains the Pancasila ideology 91%, is proud of the NKRI 92%, respects the red and white flag 94%, respects differences in 99%, coexists with other tribes 98%, respects religion and beliefs 100%, congratulate 97% of different religions. Based on the data about these perceptions, it can be seen that; First, students in Poso District have positive perceptions of nationalism (nationalism). Second, students still have a vulnerable national view, especially when connected with attitudes towards the basic existence of statehood. Third, students still have a vulnerability to religious issues, where religious sentiment can be a trigger for conflict. Fourth, students still hold the view that the life of the nation and state can only be strengthened if its citizens uphold the philosophy of the nation (Pancasila) within the framework of a unitary state.